(untitled) (AYUSHDHARA, 2021)
In present scenario the most common cause of disability in patients under 45years of age is back pain. Gridhrasi can be correlated to Sciatica where pain radiates from buttock into thigh, calf, and occasionally the foot. In the surgical treatment of Sciatica may have serious post-operative complications. Basti being superior treatment in Vatavyadhis and keeping in view of lacunae in medical management and due to the complications caused by modern surgical interventions there is a need of a safe, potent, cost effective, simple and short-term therapy for this condition. So here is an attempt to compare the effect of Matra Basti with Shuddha Bala Taila (group A) and Ksheerabala Taila (group B) in the management of Gridhrasi. Where 40 patients who fulfilled the inclusion criteria randomly and distributed into 2 groups of 20 patients each. Clinical symptoms were given grading according their severity. After completion of the treatment result were assessed and statistically analyzed to know the significance. Considering the overall effect of the treatment, comparatively patients in group B showed better results in Parameters Pain (<0.05), Stambha (<0.05), and SLR (<0.05). Whereas patients in Group A showed better results in Spandana (<0.05) where as both group patients showed equal result in Toda. So, the Ksheerabala Taila is more effective than Shuddha Bala Taila in the management of Gridhrasi.